Nevromodulacija pri zdravljenu parkinsonove bolezni, distonije in esencialnega tremorja - Trošt, Maja (Rehabilitacija (Ljubljana), 2023)
Parkinson's disease (PD) is the second most common neurodegenerative disease of the brain, after Alzheimer's disease. The symptoms and signs of the disease can be effectively alleviated with symptomatic drugs, which mostly replace the missing dopamine. When the effects of oral drugs wear off, we can use continuous treatment with levodopa, and later, if necessary, also with deep brain stimulation. The latter can also be used to treat dystonia, essential tremor and other disorders. When deciding on the treatment, it is very important to identify patients who are suitable candidates for this type of treatment, and neurorehabilitation must also follow.
Keywords: distonija; esencialni tremor; globoka možganska stimulacija; nevromodulacija; Parkinsonova bolezen; zdravljenje